The Pressure-Streamfunction MFS Formulation for the Detection of an Obstacle Immersed in a Two-Dimensional Stokes Flow (Advances in Applied Mathematics and Mechanics, 2010)
In this paper we consider a geometric inverse problemwhich requires detecting an unknown obstacle such as a submarine oran aquatic mine immersed in a Stokes slow viscous stationary flow ofan incompressible fluid, from a single set of Cauchy (fluid velocityand stress force) boundary measurements. The numericalreconstruction is based on the method of fundamental solutions (MFS)for the pressure and streamfunction in two dimensions combined withregularization. Numerical results are presented and discussed.